Magnet-Retained Two-Mini-Implant Overdenture: Clinical and Mechanical Consideration - Yuichi Ishida; H. S. Kiran Kumar; Takaharu Goto; Megumi Watanabe; Rudi Wigianto; Tetsuo Ichikawa (MDPI AG, 2016)
Two-implant overdentures have become the accepted treatment for restoring mandibular edentulism. The dimensions of regular implants sometimes limit their use, such as in the case of narrow ridges. Mini-implants with reduced diameters (less than 3.0 mm) enable insertion into narrow ridges. A magnet-retained two-mini-implant overdenture system was developed and is described in this paper. Additionally, we describe a clinical mandibular procedure using the system and evaluate its biomechanical performance.